Detection of xerostomia, Sicca, and Sjogren's syndromes in a national sample of adults - Indre Stankeviciene; Alina Puriene; Diana Mieliauskaite; Lina Stangvaltaite-Mouhat; Jolanta Aleksejuniene (BMC, 2021)
Abstract Objectives To assess the prevalence and determinants of xerostomia among adults and identify how many of the ones experiencing xerostomia have Sicca and Sjogren's syndromes. Materials and methods This cross-sectional study included 1405 35-74-year-old Lithuanians (51.7% response rate) from the five largest Lithuanian cities and 10 peri-urban and rural areas that were randomly selected from each of the 10 Lithuanian counties. Xerostomia was determined by the self-reported experience of dry mouth as "often" or "always". A dentist diagnosed Sicca syndrome by unstimulated whole sialometry and the Schirmer's test, and all cases were referred to a rheumatologist to confirm Sjogren's syndrome. Self-reported questionnaires collected data about the determinants. Results The prevalence of xerostomia was 8.0% (n = 112), Sicca syndrome was diagnosed for 8 participants (0.60%), and Sjogren's syndrome for 2 participants (0.14%), with this being the first time it was diagnosed. Experiencing xerostomia was associated with older age (OR 1.7, 95% CI 1.1-2.6), urban residence (OR 3.3, 95% CI 1.6-5.0), presence of systemic diseases (OR 2.5, 95% CI 1.4-3.3), and the use of alcohol (OR 0.6, 95% CI 0.4-0.9). The higher proportion of participants with Sicca syndrome involved females, of older age, having systemic diseases, and using medications. Conclusions The prevalence of xerostomia was 8.0% and the determinants of xerostomia were older age, urban residence, systemic diseases, and absence of using alcohol. In total, 0.6% of participants had Sicca syndrome, which was more prevalent among females, older subjects, those with systematic diseases, and those using medications. Sjogren's syndrome was diagnosed in 0.14% of participants. Clinical relevance Dental clinicians need to be trained to identify potential Sjogren's syndrome cases.